Dentist material selection for single-unit crowns: Findings from the National Dental Practice-Based Research Network. (December 2016) - Makhija, Sonia K.; Lawson, Nathaniel C.; Gilbert, Gregg H.; Litaker, Mark S.; McClelland, Jocelyn A.; Louis, David R.; Gordan, Valeria V.; Pihlstrom, Daniel J.; Meyerowitz, Cyril; Mungia, Rahma; McCracken, Michael S.; ,
Abstract: Objectives: Dentists enrolled in the National Dental Practice-Based Research Network completed a study questionnaire about techniques and materials used for single-unit crowns and an enrollment questionnaire about dentist/practice characteristics. The objectives were to quantify dentists' material recommendations and test the hypothesis that dentist's and practice's characteristics are significantly associated with these recommendations. Methods: Surveyed dentists responded to a contextual scenario asking what material they would use for a single-unit crown on an anterior and posterior tooth. Material choices included: full metal, porcelain-fused-to-metal (PFM), all-zirconia, layered zirconia, lithium disilicate, leucite-reinforced ceramic, or other. Results: 1777 of 2132 eligible dentists responded (83%). The top 3 choices for anterior crowns were lithium disilicate (54%), layered zirconia (17%), and leucite-reinforced glass ceramic (13%). There were significant differences (p < 0.05) by dentist's gender, race, years since graduation, practice type, region, practice busyness, hours worked/week, and location type. The top 3 choices for posterior crowns were all-zirconia (32%), PFM (31%), and lithium disilicate (21%). There were significant differences (p < 0.05) by dentist's gender, practice type, region, practice busyness, insurance coverage, hours worked/week, and location type. Conclusions: Network dentists use a broad range of materials for single-unit crowns for anterior and posterior teeth, adopting newer materials into their practices as they become available. Material choices are significantly associated with dentist's and practice's characteristics. Clinical significance: Decisions for crown material may be influenced by factors unrelated to tooth and patient variables. Dentists should be cognizant of this when developing an evidence-based approach to selecting crown material.